Bagaimana Stres Kerja dan Work Life Balance pada Pekerja Wanita Memediasi Work Family Conflict dengan Prestasi Kerja? - Rita Tri Yusnita; Rina Nurlinawaty (IPB University, 2022)
This study aims to determine how the effect of work family conflict on the work performance of female bank employees in Tasikmalaya City, and how work stress and work life balance mediate the relationship between work family conflict and work performance. Primary data was taken by distributing questionnaires to female bank employees in the city of Tasikmalaya. The research sample was determined through Snowball Sampling and Accidental Sampling. The questionnaire was distributed in the form of Google Form, and collected 139 respondents' answers. The data were analyzed using the variant-based Structural Equation Model method using the GeSCA program. The results showed that work family conflict directly had a significant effect on work stress, work life balance, and work performance. Meanwhile, work stress has no significant effect on work performance. However, work life balance directly has a significant effect on work performance. Work stress is not able to mediate the effect of work family conflict on work performance, while work life balance is able to mediate the effect of work family conflict on work performance.